2003
DOI: 10.1002/adma.200304898
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Silicon Nanotubes on Porous Alumina Using Molecular Beam Epitaxy

Abstract: Silicon nanotubes (SiNTs) have been grown on a porous alumina surface, without the assistance of catalysts, by molecular beam epitaxy (MBE). The flow rate of Si atoms and the corrugated porous alumina surface seem to play an important role in the continuous growth of Si tubular structures. The Figure shows a field‐emission scanning electron microscopy image of the SiNTs grown on a regular array of hexagonal porous alumina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
79
0
8

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(93 citation statements)
references
References 19 publications
2
79
0
8
Order By: Relevance
“…At full coverage with zigzag configuration, the band gap (3.8 eV) is much more than that in arch-type (0.7 eV). A band gap of 1.0 eV for full hydrogenated (5,5) tube is known to be underestimated in LDA calculation [21]. In the arch and zigzag-type, Lee et al clearly observed the band gaps of 1.63 eV and 2.63 eV, respectively [14].…”
Section: Electronic Structuresmentioning
confidence: 95%
“…At full coverage with zigzag configuration, the band gap (3.8 eV) is much more than that in arch-type (0.7 eV). A band gap of 1.0 eV for full hydrogenated (5,5) tube is known to be underestimated in LDA calculation [21]. In the arch and zigzag-type, Lee et al clearly observed the band gaps of 1.63 eV and 2.63 eV, respectively [14].…”
Section: Electronic Structuresmentioning
confidence: 95%
“…Further more, the poor p-p overlapping for Si, Si-Si = 2.16Å with bond energies equal 327Kj/mol are much weaker than the carbon-carbon bonds (1.34Å) with bond energies equal 602Kj/mol 34 …”
Section: Introductionmentioning
confidence: 94%
“…One of the main factors that impact the chemicals and physicals proper ties of Si in comparison with those of carbons are the larger atomic sizes of Si that has longer Si-Si =2.35Å bonds 34 in size and weaker bonds with the bond energies of 222,Kj/mol, comparing to carbon-carbon bonds equal 1.54Å including bond energy= 345.6Kj/mol 33 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations